2022
DOI: 10.1111/nyas.14910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of global terrestrial near‐surface wind speed simulated by CMIP6 models and their future projections

Abstract: We evaluate the performance of Coupled Model Intercomparison Project Phase 6 (CMIP6) models in simulating the observed global terrestrial near‐surface wind speed (NSWS) and project its future changes under three different Shared Socioeconomic Pathways (SSPs). Results show that the CESM2 has the best ability in reproducing the observed NSWS trends, although all models examined are generally not doing well. Based on projections of CESM2, the global NSWS will decrease from 2021 to 2100 under all three SSPs. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
4
19
1
Order By: Relevance
“…9 Conversely, the WRF-CESM2 does not better represent the past temporal variability than GCMs, and it simulates a nonsignificant increase of SWS for the historical period. Although Shen et al 16 denoted that the CESM2 has the best abilities among all the CMIP6 models globally, we found that neither CESM2 nor WRF-CESM2 outperforms other models over the IP.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…9 Conversely, the WRF-CESM2 does not better represent the past temporal variability than GCMs, and it simulates a nonsignificant increase of SWS for the historical period. Although Shen et al 16 denoted that the CESM2 has the best abilities among all the CMIP6 models globally, we found that neither CESM2 nor WRF-CESM2 outperforms other models over the IP.…”
Section: Discussioncontrasting
confidence: 86%
“…To explore the differences of using a higher horizontal resolution product, the Community Earth System Model version 2 (CESM2) has been dynamically downscaled using the WRF model. As Shen et al 16 proposed, CESM2 has the best performance in reproducing the past terrestrial global SWS. 23 The dynamic downscaling method was performed with WRFv3.8.1 using the ARW dynamic core.…”
Section: Rcm: Dynamic Downscaling With Wrfmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes can significantly impact multiple aspects of the climate system, including precipitation, ocean currents, and ecosystems. The CMIP results have shown that increasing concentrations of greenhouse gasses are driving significant changes in global wind and temperature patterns 19,24,25 . In the latest CMIP6 simulations, the influence of changes in greenhouse gasses and adaptation policies on the climate system has been assessed using scenarios termed Shared Socioeconomic Pathways (SSP)26.…”
Section: Introductionmentioning
confidence: 99%